Studi Eksplorasi Konstrak Kepemimpinan Model Jawa: Asta Brata - Moh. As’ad; Wahyu Jati Anggoro; Mariana Virdanianty (Faculty of Psychology, Universitas Gadjah Mada, 2011)
This study aims to explore the ancient Javanese leadership model: Asta Brata and develop the concept into an instrument to measure leadership. Asta Brata (Sanskrit means eight behavior) basically have a major philosophy that the art of leadership can be learned from eight nature symbols: earth, ocean, sky, stars, sun, moon, wind, and fire. Each element has different symbolic meanings which reflected the characteristic of ideal leader based on Javanese culture. Stages of the study was divided into two studies, (1) the exploration exploration construct construct leadership through content analysismanuscript texts containing the teachings of Asta Brata and (2) develop a psychological construct in order to create the scale. A total of 32 Likert scale butir successfully constructed and tested in adultsubjects (N=186). The results of the psychometric properties on a scale evaluations showed satisfactory reliability estimates (α = 0.86) and the construct validity (convergent and exploratoryfactor analysis) was pscychometrically accepted.